Use of topical corticosteroids among Danish patients with psoriasis. (2nd January 2019) - Svendsen, M.T.; Ernst, M.S.; Andersen, K.E.; Andersen, F.; Johannessen, H.; Pottegård, A.
Summary: Psoriasis is a common chronic inflammatory skin disease, affecting about 2‐4% of the population in Europe. Psoriasis negatively affects patients' quality of life and is linked to several psoriasis‐associated comorbidities (diseases that occur alongside psoriasis). Topical drugs, which means they are applied directly to the skin, are a recommended first‐line treatment for mild‐to‐moderate psoriasis, but their reported real‐life use is conflicting. This study investigated psoriasis patients' real‐life use of topical drugs and other antipsoriatic treatments. Danish researchers conducted a drug utilization study based on the nationwide Danish health registry data, including data on all patients above 18 years of age who received a first‐time hospital diagnosis of psoriasis and were prescribed at least one topical drug in the period 2005‐2015 (7, 743 patients). The patients were followed for a three‐year period after the time of diagnosis. Among many findings, the authors reported that the most frequently used topical antipsoriatic drugs were combinations containing corticosteroid with calcipotriol, accounting for 31% of the total use. Patients' use of topical drugs increased around the time of hospital diagnosis. The use also varied considerably between geographical regions as well as for the individual patients, with 25% of the patients using 70% of the total amount of topical treatment. The total use of topical antipsoriatic drugs decreased by 19% during the study period, while use of a drug called methotrexate which is taken by tablet or injection, increased by 70%. The authors concluded that the use of topical antipsoriatic drugs shows considerable diversity over time, regional practices and differences between patients. Abstract : Linked Article:  Svendsen et al. Br J Dermatol 2019;180 :157–164